The prevalence of asymptomatic Cryptococcal antigenemia in people living with human immunodeficiency virus with severe immunosuppression - Kolligouda, Manjunath G.; Khare, Rajeev L.; Dubey, Prachi; Sherwani, Nikita; Lakra, Devpriya (International Journal of Advances in Medicine, 2025)
Background: Cryptococcal meningitis is a life-threatening disease among human immunodeficiency virus (HIV) patients specially with severe immunosuppression. Cryptococcal antigen (CrAg) can be detected well before the development of disease as CrAg circulates before the progressing to meningitis so if serum CrAg positive in asymptomatic patients the patients may develop cryptococcal meningitis in future so treatment in asymptomatic patients who are positive for CrAg can reduce the mortality. Methods: This was cross-sectional study in which CrAg was tested among 84 PLHIV patient with CD4 count of less than 200/mm3 using latex agglutination test. Age, gender, World Health Organization (WHO) staging, ART regimen, haemoglobin level and presence of other opportunistic infection were added as determinants of CrAg positivity. Results: Mean age among the study subjects was 39.19 years. 72.6% were males and 27.4% were females. 77.4% belong stage 1 of WHO,6% to stage 2,15.4% to stage 3, and 1.2% to stage 4. Mean CD4 count of subjects was 94.70 cells/mm3. 54.7% of the subjects had CD4 count of less than 100cells/mm3 and 45.3% subjects had CD4 count of more than 100 cells/mm3 subjects were tested positive for CrAg with prevalence being 6%. Mean CD4 count in subjects who tested positive was 34.20 cells/mm3 and in subjects who tested negative was 98.53 cells/mm3. Conclusions: Prevalence of asymptomatic cryptococcal antigenemia was found to be 6% in PLHIV with CD4 count less than 200 cells/mm3 and prevalence was about 10.8% in subjects with CD4 count of less than 100 cells/mm3 compared to 0% in subjects with CD4 count of 100-200 cells/mm3. As the mortality of cryptococcal meningitis is very high and testing CrAg is cost effective if done in large scale.